(untitled) (Journal of the College of Education for Women, 2019)
The nature of china’s foreign policy towards the African continent was not the result of the era that came after the Cold war, but it extends to the periods of the sixties, seventies and eighties of the last century. It has been based on foreign political decision - maker of China in its dealings with African countries on many of the pillars and priorities ,and on the top of these priorities china’s economic interest,especially aftetr the Chinese economy has achieved significant growth which leads to achieve high levels of technological development that is reflected positively on the Chinese industry ,where China has become one of the largest global markets for the supply of goods to various parts of the world as the market for products of countries who have trade dealings with China . on this basis ,China has become one of the countries with economic direction in dealing with Developing countries which are in need to deal with China. Therefore, this study has highlighted the Chinese foreign policy towards Africa in terms of the goals that pushed China to move toward Africa ,and what are means used to implement the goals .then the study has concluded a future vision of China towards the continent in the light of the U.S presence in the African continent, a presence that stands in the way of the Chinese ambition in Africa because of several constraints, including: 1- China’s policy focuses only on how to get cheap natural resources and make African markets as a place for its products . 2- the cultural ties between China and Africaare weak especially the Chinese language is not widely spread in Africa ,unlike English and French.